1952
DOI: 10.1680/ipeds.1952.11272
|View full text |Cite
|
Sign up to set email alerts
|

Discussion. Recent Developments in Railway Curve Design.

Abstract: APPENDIX ~LASSIFICATION OF LINESand the type, weight, and speed of the traffic which they carry, in accordance withThe running lines of British Railways are classified according to their importance the ruling of the Railway Executive shown in Table 8. B ii C DLines subject to speeds exceeding 60 miles per hour, over which twelve or more express passenger-trsins operate regularly (winter Lines subject to speeds of 60 miles per hour and over, but not timetable) per 24 hours.qualified to be classed as A lines. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Comfort is a subjective concept which is difficult to define, and harder still to measure. Nevertheless, it has been shown that comfort decreases monotonically as a function of acceleration magnitude [20], and that most people are 'comfortable' at accelerations below 2m s −2 [15]. Higher mean accelerations will also (normally) decrease controller margins of error, and increase the likelihood of crashes.…”
Section: Performance Metricsmentioning
confidence: 99%
“…Comfort is a subjective concept which is difficult to define, and harder still to measure. Nevertheless, it has been shown that comfort decreases monotonically as a function of acceleration magnitude [20], and that most people are 'comfortable' at accelerations below 2m s −2 [15]. Higher mean accelerations will also (normally) decrease controller margins of error, and increase the likelihood of crashes.…”
Section: Performance Metricsmentioning
confidence: 99%